PROFILE WHEEL WITH ADDITIONAL SURFACE CATHANIA FOR IMPROVEMENT OF RELATIVE INTERMEDIATE VEHICLE WITH A CURRENT DISTRIBUTOR SMALL RADIUS (Transport systems and technologies, 2018)
A special feature of urban rail transport is the presence of small curves with a radius of 17 meters, which requires increased attention. Movement in such curves leads to an increase in the impact on the path, an increase in the resistance of the vehicle, a slip in the wheel-rail contact, accelerated wear of the contact pair, and an increase in noise. In order to reduce the slip in the wheel-rail contact when a tram passes a curved section of a path of small radius, a wheel profile design with two rolling surfaces is proposed, as well as a specific curved track section design. The proposed method of movement of the wheelset in a curve in which an ordinary wheelset can not provide rolling motion. The expediency of the present invention is demonstrated by simulating the movement of a tram car in an S-shaped curve.
Keywords: sliding speed in the contact “wheel - rail”, a curved part-runway with a small radius, a wheel profile with two rolling surfaces.